2005
DOI: 10.1158/1078-0432.ccr-05-0050
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of In vitro and In vivo Tumor Cell Radiosensitivity by the DNA Methylation Inhibitor Zebularine

Abstract: Aberrant DNA hypermethylation is a frequent finding in tumor cells, which has suggested that inhibition of DNA methylation may be an effective cancer treatment strategy. Because DNA methylation affects gene expression and chromatin structure, parameters considered to influence radioresponse, we investigated the effects of the DNA methylation inhibitor zebularine on the radiosensitivity of human tumor cells. Three human tumor cell lines were used in this study (MiaPaCa, DU145, and U251) and the methylation stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 45 publications
8
95
0
2
Order By: Relevance
“…Consequently, it is possible that zebularine acts to impede nucleotide excision repair or restore p53 activity by unknown mechanisms unrelated to activity of hMLH1. In support of this conjecture, a recent study showed that zebularine increased radiosensitivity of tumor cells, likely by inhibition of DNA repair (57). Although 5-aza-dC treatment resulted in sensitization to cisplatin in our system (similar to zebularine), clinical trials of that combination have been quite discouraging, resulting in significant toxicity (58,59).…”
Section: Discussionmentioning
confidence: 57%
“…Consequently, it is possible that zebularine acts to impede nucleotide excision repair or restore p53 activity by unknown mechanisms unrelated to activity of hMLH1. In support of this conjecture, a recent study showed that zebularine increased radiosensitivity of tumor cells, likely by inhibition of DNA repair (57). Although 5-aza-dC treatment resulted in sensitization to cisplatin in our system (similar to zebularine), clinical trials of that combination have been quite discouraging, resulting in significant toxicity (58,59).…”
Section: Discussionmentioning
confidence: 57%
“…Although this drug works in a manner similar to 5-Aza-CR and 5-Aza-CdR, it is more stable and less toxic than 5-Aza-CR and 5-Aza-CdR DNMTis (Zhou et al, 2002;Cheng et al, 2003). In line with these findings, zebularine has been shown to reactivate tumor suppressor genes (Flotho et al, 2009;Billam et al, 2010), enhance tumor cells' chemotherapy and radiation sensitivity (Dote et al, 2005), exert angiostatic and antimitogenic activities (Balch et al, 2005;Hellebrekers et al, 2006) and to be stable enough for oral administration (Zhou et al, 2002;Cheng et al, 2003). In addition, at low doses, zebularine can be given to patients continuously without the overt cytoxicity associated with 5-Aza-CR and 5-Aza-CdR.…”
Section: Dna Methyltransferase Inhibitors (Dnmtis)mentioning
confidence: 76%
“…Dote et al23 found the enhancement of tumor cell radio‐sensitivity by the DNMT inhibitor (zebularine) in vitro and in vivo. Treating cells with zebularine, the radio‐sensitivity of 3 human tumor cells, including pancreatic carcinoma, glioblastoma, and prostate carcinoma, were more sensitive than control groups.…”
Section: Radio‐sensitivity and Dna Methylation Of Dna Damage Repair‐rmentioning
confidence: 99%
“…To investigate the role of DNA methylation inhibitor in tumor radio‐sensitivity, researchers studied 3 human tumor cell line (pancreatic carcinoma, glioblastoma and prostate carcinoma) 23. Hyper‐methylated in cancer 1 ( HIC1 ) gene is a growth regulatory and tumor repressor gene.…”
Section: Radio‐sensitivity and Dna Methylation Of Cell Proliferation‐mentioning
confidence: 99%